2004
DOI: 10.1080/01140671.2004.9514281
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of pesticides toHalmus chalybeus(Coleoptera: Coccinellidae) and the effect of three fungicides on their densities in a citrus orchard

Abstract: The effect of three fungicides in five programmes on densities of Halmus chalybeus (steelblue ladybird) was tested in a citrus orchard. Programmes of five and nine applications of cupric hydroxide or chlorothalonil reduced densities by c. 35% and 70% respectively, compared with unsprayed plots. One application of copper sulphate and lime (Bordeaux mixture) reduced ladybird density by 81%, similar to the two nine-application programmes. These reductions in numbers were probably due to a repellent effect since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Copper at high concentrations may damage the DNA structure and is considered toxic to arthropods (Bernabò et al 2017). Other studies indicate that Copper has negative effects on beneficial organisms, such as Apis mellifera Linnaeus (Hymenoptera: Apidae) causing high larval mortality after seven days of exposure and slowed larval development, caused reduction in pre-pupal and pupal weights, decreased the survival rate of both larvae and foragers (Di et al 2016), high mortality of predator Halmus chalybeus (Boisduval) (Coleoptera: Coccinellidae) (Lo 2004), and parasitoid T. remus (Silva et al 2016). Few studies evaluated the lethal and principally sublethal effects of these compounds, highlighting the importance of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Copper at high concentrations may damage the DNA structure and is considered toxic to arthropods (Bernabò et al 2017). Other studies indicate that Copper has negative effects on beneficial organisms, such as Apis mellifera Linnaeus (Hymenoptera: Apidae) causing high larval mortality after seven days of exposure and slowed larval development, caused reduction in pre-pupal and pupal weights, decreased the survival rate of both larvae and foragers (Di et al 2016), high mortality of predator Halmus chalybeus (Boisduval) (Coleoptera: Coccinellidae) (Lo 2004), and parasitoid T. remus (Silva et al 2016). Few studies evaluated the lethal and principally sublethal effects of these compounds, highlighting the importance of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, insecticides were not so likely to explain variability in the natural enemies of those pests, suggesting that the products used by these growers were preferentially affecting the pests and not the beneficial natural enemies. These results provide some reassurance that using selective insecticides such as buprofezin, CpGV and tebufenozide or methoxyfenozide, which have few effects on nontarget insects (Rumpf et al ., ; Shaw et al ., ; Lo, ; Shaw and Wallis, ; Rogers et al ., ; Beers et al ., ), can preserve biological control services, as intended in integrated pest management systems. The involvement of fertilizers, in conjunction with insecticides, in the best models to explain pests caught on sticky traps suggests that further research to examine the influence of fertilizers on the effectiveness of insecticides against apple pests could yield useful information for optimizing pest control practices.…”
Section: Discussionmentioning
confidence: 99%
“…Fungicides also featured in some models explaining variability in pest, natural enemy, parasitoid and predator assemblages caught in pitfall traps and marginal tests indicated that dithianon and penconazole on their own could explain significant amounts of variability. The inclusion of fungicides in toxicity tests with nontarget species of interest (Lo, ) could yield useful data for optimizing the use of pest and disease control agrichemicals on orchards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese wax scale is considered a key pest of citrus in Australia and New Zealand (Smith et al , 1997; Lo, 2004); however, in the Mediterranean Basin, it is considered a secondary pest, because its populations usually remain below economic injury levels due to unfavourable environmental conditions, natural enemies and sprays performed to control other citrus pests. Nevertheless, local outbreaks occasionally occur in the western countries of the region, especially on clementine varieties (García-Marí et al , 1994; Katsoyannos, 1996; Stathas et al , 2003).…”
Section: Introductionmentioning
confidence: 99%